Following the trail of the grey brocket deer (Mazama gouazoubira) in Argentina: new locality records, activity patterns and habitat use - Rodríguez, Daniela; Fleitas Quintana, Roco; Zeverini, Diego; Tagua, Mariano; Lucero, Jesús Luis; Szymañski, Carolina (THERYA, 2024)
The brown brocket deer (Mazama gouazoubira) is a species of neotropical ungulate that inhabits several countries in South America. In Argentina, it is distributed in the northern portion of the country, while historical records do not mention it in the province of Mendoza. However, in the Categorization of Mammals of Argentina (2019), the NE of Mendoza is proposed as a potential distribution area of the species. In this work we confirm the presence of the brown brocket deer in the province of Mendoza (locality of Desaguadero - RAMSAR Site), and we also evaluate its activity patterns and habitat preferences. We established 1 km2 grids in three environments: salt flats, shrublands, and forests. A camera trap (n = 38) was placed in each grid, active for 55 days between October 2022 and April 2023 for fauna survey. In addition, NDVI values (Normalized Difference Vegetation Index) were calculated from LANDSAT-8 images as an estimator of vegetation cover for each grid. We obtained 25 independent records of 11 individuals (5 males and 6 females) from a sampling effort of 51,072 hours of camera operation (2,090 night/trap = 55 night * 38 camera). The males were individually identified based on the presence of antlers, their size, dimension and texture, while the females by their body size and gestation condition. In terms of activity patterns, we observed that these animals are most active in the afternoon (16 to 19 hs) and morning (8 to 9 hs), avoiding the moments of greatest solar radiation (Rayleigh-test r = 0.99, p < 0.001). NDVI was significantly different among the three environments (Chisq = 32.98; p < 0.001), with the forest having the highest vegetation cover. Finally, generalized linear models with binomial distribution were used to evaluate the effect of vegetation on the presence of brown brocket deer. We found that the higher the NDVI value, the higher the probability of presence of the deer (z = 2.27; p < 0.05). These results expand the distribution of the species and increase the diversity of mammals for Mendoza province, which generates added value to the planning of the proposed protected area for Desaguadero in the RAMSAR site Lagunas de Guanacache, Desaguadero y del Bebedero.